Development of Orange Grading Machine on Weight Basis - Gaikwad, Nilesh N.; K. Samuel, D. V.; Grewal, Manpreet Kaur; Manjunatha, M. (Journal of Agricultural Engineering, 2015)
High value fresh agricultural produce such as orange must be carefully handled and graded in order to meet customerdemands and quality standards. Manual grading is widely adopted practice which is costly and time consuming. The existing mechanical graders grade fruits on the basis of size, and owing to mechanical nature have limitations of lower capacity and efficiency. The present work describes the development of electronic grading machine on weight basis for oranges. The machine comprised of various elements such as feeding unit, weighing assembly, droppingand collection unit. The machine is capable of individually metering fruits in weighing section and weighing of individual fruits and grading them in four different weight grades.